Tepung Labu Kuning (Cucurbita moschata), Tepung Porang (Amorphophallus muelleri Blume), dan Kombinasi Kedua Tepung sebagai Penurun Gula Darah dan Peningkat Motilitas Spermatozoa Mencit (Mus musculus) - Sukarjati, Sukarjati; Evarina, Melinda Yuti; Andriani, Vivin (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Diabetes Mellitus (DM) is a global epidemic with high morbidity and mortality. Diabetes Mellitus (DM) is thought to have a negative impact on sperm quality. Yellow pumpkin contains antioxidants that can neutralize free radicals which can improve fertility. Glucomannan is a substance contained in porang which functions as a soluble fiber and plays a role in blood glucose balance. This study aims to examine pumpkin flour, porang flour and a combination of both flours on sperm motility and body weight of alloxan-induced diabetic mice. This study used 25 mice aged 3 months, body weight 25gr-30 gr. This study used a completely randomized plan (CRD) with 5 replications and 5 treatments. The treatments were negative control (diabetic mice), positive control (administration of glimepiride at a dose of 0.0078 mg/mice per day), D1 (pumpkin flour 134.4 mg/30g BW of mice), D2 (porang flour 63mg/30g BW mice), D3 (combination 50% : 50% = 67.2 mg : 31.5 mg/30 grBW mice). Diabetic mice were made by intraperitoneal induction of alloxan dose of 200 mg/Kg for 3 days. The parameters observed were spermatozoa motility, body weight and blood sugar levels of the mice. The research data were analyzed using the ANOVA test followed by the BNT test. The results showed that the administration of glymeride, pumpkin flour, porang flour and their combination had a significant effect on reducing blood sugar (p=0.000) and sperm motility (p=0.000), but had no effect on body weight (p=0.317). Conclusion: pumpkin flour, porang flour or a combination of both flours can be used as herbs to lower blood sugar and increase sperm motility in diabetes sufferers.